Medieval period, book 2. - Byrne, Robert; Milliken Publishing Company (1971)
Focuses on the crusades, the Gothic style, the Hundred Years War, the Great Schism, and other aspects of medieval life in Europe.
With teacher's guide and duplicating masters.
Keywords: Middle Ages -- History; Middle Ages -- History; World history -- Medieval Period .; Europe -- History -- 476-1492.; Europe -- History -- 476-1492.